Influence of relative humidity on prolonged exercise capacity in a warm environment - Maughan, R. J.; Otani, H.; Watson, P. (European Journal of Applied Physiology, 2012)
This study examined the influence of relative humidity on endurance exercise performance in a warm environment. Eight male volunteers performed four cycle exercise trials at 70% maximum oxygen uptake until volitional exhaustion in an environmental chamber maintained at 30.2 ± 0.2°C. Volunteers were tested under four relative humidity (rh) conditions: 24, 40, 60 and 80%. Core and weighted mean skin temperature, heart rate, skin blood flow, and cutaneous vascular conductance were recorded at rest and at regular intervals during exercise. Mean ± SD time to exhaustion was 68 ± 19, 60 ± 17, 54 ± 17, and 46 ± 14 min at 24, 40, 60, and 80% rh, respectively (P < 0.001); exercise time was significantly less at 60% (P = 0.013) and 80% (P = 0.005) rh than recorded at 24% rh. There were no differences in core temperature (P = 0.480) and heart rate (P = 0.097) between trials. Core temperature at exhaustion was 39.0 ± 0.3°C at 24, 40, and 60% rh and 39.1 ± 0.3°C at 80% rh (P = 0.159). Mean skin temperature at the point of exhaustion was higher at 80% rh than at 24% rh (P < 0.001). Total sweat loss was similar between trials (P = 0.345), but sweating rate was higher at 60 and 80% rh than at 24% rh (P < 0.001). The results suggest that exercise capacity at moderate intensity in a warm environment is progressively impaired as the relative humidity increases.